I-VRenewal: A cloud based system for VISA renewal: A case study of IIUM - Islam, Thouhedul; Olanrewaju, Rashidah Funke; Ajayi, Binyamin Adeniyi (IEEE, 2016)
Getting visa or its renewal is one of the important elements for International students studying abroad. Each and every year students need to renew their visa, to extend their studentship in order to stay in a particular country. In Malaysia, in order to process visa renewal faster, Education Malaysia Global System (EMGS) was introduced by Malaysian Government. Since the implementation of EMGS in April 2015 at International Islamic University Malaysia (IIUM), however renewal process has become complex and lengthy. As a result, many international students faced difficulties in visa application which cost lot of money, time and resources. This paper evaluates the current system of student visa application at IIUM and proposes an intelligent cloud-based system for visa renewal that is more efficient.